2019
DOI: 10.1101/722041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bee visitation and fruit quality in berries under protected cropping vary along the length of polytunnels

Abstract: 15Wild and managed bees provide effective crop pollination services worldwide. Protected 16 cropping conditions are thought to alter the ambient environmental conditions in which 17 pollinators forage for flowers, yet few studies have compared conditions at the edges and 18 centre of growing tunnels. We measured environmental variables (temperature, relative 19 humidity, wind speed, white light and UV light) and surveyed the activity of managed 20 honeybees Apis mellifera, wild stingless bees Tetragonula carbo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…We aimed to determine if honeybee and other insect numbers differed between the edge and middle of the polytunnels as observed in previous studies [ 30 ] ( Fig 5 ). We compared insect counts at the edges of the polytunnels (Strawberries: 1–12 meters from the edge; Raspberries: 1–5 meters from the edge) with the middle of the polytunnels (Strawberries: 35–52 meters from the edge; Raspberries: 22–26 meters).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to determine if honeybee and other insect numbers differed between the edge and middle of the polytunnels as observed in previous studies [ 30 ] ( Fig 5 ). We compared insect counts at the edges of the polytunnels (Strawberries: 1–12 meters from the edge; Raspberries: 1–5 meters from the edge) with the middle of the polytunnels (Strawberries: 35–52 meters from the edge; Raspberries: 22–26 meters).…”
Section: Methodsmentioning
confidence: 99%
“…Polytunnels aid in the manipulation of the microenvironment, usually for the benefit of crop plants. Research by Hall et al (2019) [30] found that the centres of polytunnels experience higher temperatures and reduced wind speed, but also lower abundances and fewer visits from stingless bees and honeybees, than the edges [30]. Thus, it appears that polytunnels may impact pollinator access, diversity, abundance, distribution, and plant reproduction/crop yield, raising questions about how to monitor and improve this increasingly common and important horticultural infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Bee colonies may alternatively be placed directly into such enclosures for pollination. However, potential risks to their use as such, and in structures such as glasshouses and tunnels, include reduced pollination efficiency and quality of yield [71,72], as well as increased vectoring of plant diseases such as viruses [73,74]. Further conflicts may need to be managed between the ability of UV-absorbing screening to suppress pest activity, for instance in whitefly and thrips [75], versus its negative effect on the foraging activity of bees [76] and parasitoids [77].…”
Section: Pollinator-friendly Cultural Physical and Mechanical Controlmentioning
confidence: 99%
“…In addition, honey bees sometimes find carrot and onion seed crops less attractive than other nearby forage sources, and thus leave the target crop to forage elsewhere [89]. In protected crops, enclosure coverings can also compromise the ability of honey bees to navigate and forage normally [91,92]. Given the substantial reliance on managed honey bees to pollinate vegetable seed crops, and the challenges that this can present for achieving reliable yields in some situations, efforts to develop alternative pollinators for use in this context are warranted.…”
Section: Vegetable Seed Cropsmentioning
confidence: 99%
“…Foraging bees rely on the sun as a primary reference for navigation and communication, and thus, cloudy conditions and protective cropping systems can negatively impact on foraging activity [91,92]. In contrast, blow flies show potential as pollinators for the greenhouse industry, as they may be less sensitive to heat, humidity, solar radiation and UV distortion than honey bees.…”
Section: Distribution and Foraging Behaviourmentioning
confidence: 99%